Proses Konseling Individual Oleh Psikologi Di Polres Tanah Datar Terhadap Anak Sebagai Korban Pencabulan Dan Dampak Psikologinya Bagi Korban - Yeni Elvitasari; Masril Masril; Wahidah Fitriani (Jurnal Pendidikan dan Konseling (JPDK), 2022)
The purpose of this writing is to find out and describe the process of implementing individual counseling carried out by psychologists for victims of sexual abuse whose cases are being handled at the Tanah Datar Police and to find out the psychological impact of implementing counseling on victims of sexual abuse, as well as the obstacles in implementing individual counseling. The type of research that the authors use is a case study. The results of the study found that the individual counseling process carried out by psychologists was carried out in three stages, namely the initial stage, the working stage, and the final stage. Individual counseling is carried out for the benefit of justice and overcoming the psychological trauma that a child has as a victim of sexual abuse. From the implementation of counseling which was carried out on three victims of sexual abuse, it did not have an impact on the psychological condition of the victims. This is because counseling is only carried out in 1-2 sessions which focus on obtaining information about the incident of sexual abuse experienced by the victim so that it does not have an impact on the feelings of fear, shame, depression and trauma that the victim has. Obstacles found in the implementation of counseling are the level of trauma that the victim has which makes the victim closed and the limited means of implementing counseling